Ovarian endometrioma increases the embryo aneuploid rate: an analysis of 7092 biopsied blastocysts from fertile monogenetic disease carriers - Niwei Yan; Xi Yuan; Sunxing Huang; Huiying Jie; Jing Wang; Yuan Yuan (BMC, 2023)
Abstract Background Endometriosis affects many reproductive aged patients with fertility decline and poor outcomes of assisted reproductive treatments, mainly by decreased ovarian reserve and lower fertilization and implantation rates. In recent decade, altered oocyte microenvironments and abnormal spindle organization have been reported to be critical to oocyte chromosomal segregation, organization and aneuploid formation. However, clinical evidences are still limited on whether endometriosis influences oocyte and embryo development. We aimed to figure out the impact of endometrioma on embryo aneuploid formation. Method This retrospective cohort study included 1,021 patients (7,092 biopsied embryos) from January 2012 to December 2020. Fertile patients without a history of miscarriage who underwent PGT-M treatment with aneuploid screening were included. Patients with ovarian endometrioma were defined as the study group, while patients without endometriosis were defined as the control group. All demographic, controlled ovarian stimulation treatment and aneuploid screening data were recorded and compared. Results The incidence of endometrioma in our study population was 6.5%. There were 7,092 embryos biopsied in total, with 308 embryos in the study group and 6,784 embryos in the control groups. The demographic characteristics were comparable between the two groups except the basal FSH level (6.02 IU/L vs. 5.52 IU/L, p = 0.012). The euploid rate of the study group was significantly lower than that of the control group (52.6% vs. 61.8%, p = 0.012), while the oocyte maturation, fertilization, usable embryo and blastocyst formation rates were comparable. Adjusted for basal FSH level, starting stimulating gonadotropin dosage, total gonadotropin dosage and FSH level on hCG day, euploid rate was still negatively related to endometrioma status. Conclusions Endometrioma status disturbs oocyte and embryo development. For infertile patients with endometrioma who require assisted reproductive treatment, pre-treatment is necessary to improve treatment outcomes. Trial registration Not applicable.